Development of the can crusher machine - Che Mohd Akhairil Akasyah, Che Anuar (2008)
Designing and fabrication the can crusher machine is a product that fulfills the customer needs. This project uses many materials such as sheet metal, hollow steel bar and others. Overall, this project involves many processes, starting from the design concept, fabrication and assembling procedures. Even though there are many types of the can crusher machine in the market, the completion of this new model provides a more practical usage.